Medical law review. (Oxford : Oxford University Press, 1993)
The Medical Law Review is established as an authoritative source of reference for academics, lawyers, legal and medical practitioners, law students, and anyone interested in healthcare and the law. The Review presents articles of international interest which provide thorough analyses and comment on the wide range of topical issues that are fundamental to this expanding area of law. In addition, commentary sections provide in depth explorations of topical aspects in the field.
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: Medical laws and legislation -- Great Britain -- Periodicals; Medical laws and legislation -- Periodicals; Medical jurisprudence -- Great Britain -- Periodicals; Medical jurisprudence -- Periodicals